Locational Analysis of Firms' Activities from a Strategic Perspective (Springer Singapore, 2018)
This book presents a variety of research papers on factories' locations, city systems, and regional development. Consisting of three parts, it provides insights into the locational aspects of firms' activities from a strategic perspective. Part 1 discusses decision-making in the context of location, specifying the motivation for firms to move their factories provided by the corporate tax system. It also presents a case study from East Asia to clarify a mechanism by which firms move factories. Part 2 addresses city systems, offering theoretical clues to understanding why city systems are important to regional economies. It also clarifies from the empirical analysis the relations between city systems and the performances of regional economies. Part 3 investigates the topic of industrial parks, demonstrating how they form a basis for establishing industrial clusters in regional economies. In addition, it examines the economic phases, such as economic disparity, generated in the process of development.